Autoimmune Demyelinating Polyneuropathy as a Manifestation of Chronic Graft-versus-Host Disease after Adult Cord Blood Transplantation in a Patient with Chronic Lymphocytic Leukemia - Fredrick Hogan; Melhem Solh (Case Reports in Hematology)
Immune mediated demyelinating disease after allogeneic stem cell transplantation is a rare entity with unclear etiology. Acute inflammatory demyelinating polyneuropathy (AIDP) has been reported after related and adult unrelated allogeneic stem cell transplantation but no such case has been reported after unrelated cord blood transplantation. We hereby present the first case of AIDP after double umbilical cord blood transplantation (DUCBT). A 55-year-old man with chronic lymphocytic leukemia (CLL) received a cord blood transplant for relapsed refractory disease with high risk cytogenetics. On day 221, patient presented with skin rash, tingling in both lower extremites, and ascending paralysis that progressed rapidly over the course of 2 days. The workup resulted in a diagnosis of AIDP and administration of intravenous immunoglobulins plus steroids was initiated. Motor and sensory powers were fully recovered and his chronic GVHD was managed for several months with single agent sirolimus.